Employee Engagement Strategies in the Era of Remote Work: Exploring Best Practices and Challenges - Hilmawan, Ipan (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This research aims to explore the role of organizational culture in maintaining employee engagement in the remote work era and identify effective cultural adaptation strategies. Through a comprehensive literature review, this research combines the concepts of organizational culture and employee engagement specifically in the context of remote work. The research results show that a strong and adaptive organizational culture can be a foundation that supports employee engagement, even when they work remotely. The implications of this research include practical recommendations for companies in managing their organizational culture in the era of remote work, as well as highlighting limitations and future research directions.